The Diagnostic and Therapeutic Challenges of Posttraumatic Iris Implantation Cysts: Illustrative Case Presentations and a Review of the Literature - Nandini Venkateswaran; Steven S. T. Ching; William Fischer; Frank Lee; Gabrielle Yeaney; Holly B. Hindman (Case Reports in Ophthalmological Medicine)
Posttraumatic iris implantation cysts are rare ocular findings that are often associated with poor visual outcomes. Iris implantation cysts can present clinicians with diagnostic and therapeutic challenges given their variable presentations and frequently destructive nature. In this paper, we provide descriptions of two unusual cases of posttraumatic iris implantation cysts. The first case is of a recurrent keratin-filled iris implantation cyst that developed after open globe injury and intraocular implantation of cilia and was treated with cyst debulking procedures, injections of 5-Fluorouracil, and iridocyclectomy. The second case is of recurrent posttraumatic serous iris implantation cysts that were treated with laser, cyst aspiration, and injections of 5-Fluorouracil. We use these cases as a platform to discuss the different manifestations of implantation cysts, the roles of anterior segment optical coherence tomography, ultrasound biomicroscopy, and histopathology in facilitating timely and accurate diagnosis and review the range of available therapeutic modalities. We discuss conservative treatment approaches, including the novel use of 5-Fluorouracil therapy as an adjunct therapy, as well as more aggressive surgical excision requiring ocular reconstruction. Through a discussion of these cases and review of the literature, we provide recommendations to assist clinicians in managing this uncommon but vision-threatening condition and minimizing complications.